Productivity Patterns in English-Uzbek Digital Content Lexicon - Usmonova, Gavharoy; Tuktakhodjaeva, Zulfiya Tukhtaevna (The Lingua Spectrum, 2026)
This article examines how “digital content vocabulary” becomes productive in English and Uzbek under platform-driven communication routines. Using the conceptual base and supplementing it with open-access research on Uzbek social-media borrowings and corpus-oriented tracking, we treat productivity as the capacity of word-formation patterns not single words to generate new, socially acceptable forms. The comparison highlights different “engines” of expansion. English often amplifies productivity through conversion and minimal-derivation action verbs (e.g., feature-to-verb shifts), blending, and hashtag-like strings that function as searchable metadata. Uzbek, by contrast, frequently reaches productivity through borrowing plus integration: imported digital terms become reusable once they accept Uzbek inflection/derivation and stabilize in everyday platform writing, alongside systematic compression conventions (abbreviations and reduced spellings).